EFFECTS OF THIRD PARTY LOGISTICS ON SUPPLY CHAIN PERFORMANCE IN KENYA (A CASE OF EAST AFRICAN BREWERIES LIMITED COMPANY) - Bwari, Maina Mildred; Getuno, Dr. Pamela; Kiarie, Dr. David (IJRDO - Journal of Applied Management Science, 2016)
The purpose of the study was to establish the effects of 3PL on supply chainperformance in East African Breweries Limited. The study specifically sought todetermine the effect of inventory control, distribution management, transportationmanagement and warehousing services on supply chain performance in East AfricanBreweries Limited. The study adopted descriptive research design. The study targetedall the 1653 employees in EABL. The sampling frame in this study was 242 staff inprocurement department, 388 in production, 357 in logistics, 108 in finance, 334 insales & marketing and 224 in quality assurance department. The study adoptedstratified random sampling technique to select the sample size of the study where thepopulation was grouped into stratus. From each stratum the study took a 10% sampleto give a sample size of 165 respondents. The study collected primary data through aquestionnaire. A pilot study of the questionnaire was done prior to the actual datacollection to test for validity and reliability. The questionnaire was administered to therespondents through drop and pick later method. The study generated qualitative andquantitative data. Both descriptive and inferential statistics were adopted for the study.Descriptive statistics included use of frequency distribution tables and measures ofcentral tendency, measures of variability and measures of relative frequencies whileinferential statistics included regression analysis. Data was presented using tables,charts, graphs. Inferential statistics was used to determine the relationship between thevariables. The study found out that inventory control, distribution management,transportation management influenced supply chain performance to a great extent butwarehousing management services influenced supply chain performance to a moderateextent. The study concluded that there is a positive and statistically significantrelationship between supply chain performance and inventory control, distributionmanagement, transportation management services provided. The study recommendedthat there is need to strategically analyze the needs of the company and the non-corebusiness so as to make informed decisions of the right logistics services to outsource.There is need for the management of EABL to improve transport efficiency as this couldchange the overall performance of the logistics system.